2000
DOI: 10.1002/1521-3765(20000804)6:15<2854::aid-chem2854>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

New Dyes Based on Amino-Substituted Acridizinium Salts-Synthesis and Exceptional Photochemical Properties

Abstract: The novel amino-substituted acridizinium salts 5a and 5b represent a new class of cyanine dyes which exhibit intense color along with efficient fluorescence properties. These dyes show moderate solvatochromism in their absorption and emission spectra. The absorption and emission shifts of the two chromophores display a reasonable correlation with solvent parameters such as donor and acceptor number. It was found that the dyes 5a and 5b interact with DNA, with quenching of the band intensies accompanied with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Indeed, several donor-substituted benzo[b]quinolizinium derivatives are known; 45,46,91 and along these lines we demonstrated that especially the amino-substituted derivatives closely resemble a rigidified hemicyanine-type dye. 92,93 As a result of the amino-substitution these derivatives exhibit significantly red-shifted absorption with a pronounced chargetransfer band ( Figure 2). 94 Specifically, the comparison of the amino derivatives with the parent compound 2a or the bromo-substituted derivative 2e demonstrates the impact of the amino group on the characteristic dye properties of this class of compounds.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, several donor-substituted benzo[b]quinolizinium derivatives are known; 45,46,91 and along these lines we demonstrated that especially the amino-substituted derivatives closely resemble a rigidified hemicyanine-type dye. 92,93 As a result of the amino-substitution these derivatives exhibit significantly red-shifted absorption with a pronounced chargetransfer band ( Figure 2). 94 Specifically, the comparison of the amino derivatives with the parent compound 2a or the bromo-substituted derivative 2e demonstrates the impact of the amino group on the characteristic dye properties of this class of compounds.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…DFT calculations have shown that the red-shifted long-wavelength bands correspond to ICT transitions that involve the transfer of electronic density from the exocyclic amino groups to the cationic hetarene upon excitation. 92 In water solution, the compound has an absorption maximum at λ max = 385 nm with a redshifted shoulder corresponding to the CT band that tails off at ca. 480 nm.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…2,6 Thus, 4-(methylsulfanyl)benzyl bromide (4b) was prepared from the commercially available 4-(methylsulfanyl)benzyl alcohol (4a) following the published procedure 16 and allowed to react with (1,3-dioxolan-2-yl)pyridine (5), 17 to give the quaternary salt 6 almost quantitatively. The cyclodehydration of the salt 6 in PPA, which is most widely used as a cyclization medium in such reactions, 2 gave only a moderate yield of the desired product (42%); however, the use of methanesulfonic acid led to an increase of the yield on this stage up to 81%.…”
Section: Synthesis Of 9-(methylsulfanyl)acridiziniummentioning
confidence: 99%
“…Moreover, we have observed that the readily available benzo[b]-quinolizinium salts (acridizinium salts) 2a,b exhibit pronounced DNA-binding properties. [15] To investigate further the photobiological features of quinolizinium derivatives we have synthesized the novel indolo[2,3-b]-quinolizinium bromide 3-Br. The interactions of this aromatic dye with DNA seemed to be of special interest since it closely resembles the structure of the known anti-tumor drug Céliptium ® (4) and that of the antibacterial and antimalarial alkaloid cryptolepine (5).…”
Section: Introductionmentioning
confidence: 99%